Improving electrochemical sensor performance for detection of 3-MCPD based on moleculary imprinted polymer-Nd2O3-Graphene - Febi Indah Fajarwati; Ganjar Fadillah; Rahmat Hidayat (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2025)
Palm oil is a key raw material in the food industry with significant strategic value. However, during the refining and deodorization processes, it can produce 3-monochloropropane-1,2-diol (3-MCPD), a compound known to be carcinogenic. Therefore, a detection method with high selectivity and sensitivity is essential. In this study, an electrochemical sensor based on molecularly imprinted polymers (MIPs) was developed and integrated with neodymium oxide–graphene (Nd₂O₃/Gr) nanocomposites. Characterization techniques such as Fourier Transform Infrared Spectroscopy (FTIR), X-ray Diffraction (XRD), and Scanning Electron Microscopy (SEM) confirmed the successful fabrication and favorable morphology of the MIPs–Nd₂O₃/Gr composites. The sensor’s performance was evaluated using Differential Pulse Voltammetry (DPV) and cyclic voltammetry methods. The incorporation of Nd₂O₃ and graphene significantly enhanced the sensor’s ability to detect 3-MCPD, demonstrating excellent linearity (R² = 0.9932) across a wide concentration range. Moreover, pH was found to play a critical role in low-concentration detection, influencing the sensor’s response. These findings indicate that the MIPs–Nd₂O₃/Gr sensor offers high selectivity and sensitivity, making it a promising candidate for monitoring 3-MCPD levels in food products and enhancing food safety control.